Exploring Cultural Humility as a Framework for Supervising Second-Language Nursing Students Writing Their Bachelor's Thesis: A Qualitative Study. - Roed, Marte Bodil; Moerch, Monica Nilsen; Hamre, Nina Beate; Loennebotn, Marianne (Nursing Reports, 2026)
Background/Objective: Colleges and universities worldwide are experiencing an increase in students from diverse cultural and linguistic backgrounds. Nursing students who study in a second language face both theoretical and practical challenges within their study programs. If these challenges are unaddressed, they may have implications for third parties such as employers, patients, and colleagues. The bachelor's thesis challenges students' understanding of a chosen subject within nursing, in addition to research skills and academic writing abilities. Effective student learning and final thesis results often rely on supervisors who are interested in and motivated by the students' success. Thus, the aim of this study was to explore supervisors' experiences and perceptions of supervising undergraduate second-language (L2) nursing students in their bachelor's thesis work. Methods: A qualitative research approach was employed to collect and analyze data. Components of Systematic Text Condensation were used for sorting and coding, and Interpretive Description was applied in the interpretive analysis. Results: Four prominent conceptual themes were agreed upon by the researchers: (1) uncertainty and cultural barriers, (2) cultural considerations, (3) teaching strategies, and (4) supervisor integrity. The conceptualized themes were found to align with the five identified attributes of cultural humility; openness, self-awareness, egolessness, supportive interaction, self-reflection and critique. Conclusions: This study suggests useful insights and practical guidance to supervisors on central issues to consider and reflect upon when guiding nursing students who are writing their bachelor's theses in a second language. The theory of cultural humility, including the identified attributes, appears to be a useful framework for supervisors when guiding L2 nursing students.